CCAFS Investment-Oriented Outcome Pathways: Lessons and New Directions - Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This paper explores how CCAFS’ work influences the investment decisions of others and what strategies are being pursued to reach a diverse range of investors globally. Outcomes and lessons from case studies and project outcomes of investment-focused research projects implemented over the last 10 years in many countries are examined. Interviews with project leaders and other key informants elicited insights on strategies and tactics that have and have not been working with respect to reaching CCAFS’ goal of substantially increasing investment, by both public and private sector actors and institutions, in climate-smart agriculture and more sustainable food systems globally. Multiple investment-oriented outcome pathways and entry points for CCAFS teams to influence public and private sector actors are explored through specific project experiences. Future pathway refinements that start with novel joint problem definition approaches with targeted partners in specific geographies/regions and markets are suggested. These can build on the valuable lessons learned to date in this unique program about how to influence a wide range of investors and contribute to significant increases in investment in these complex global challenges.